2015
DOI: 10.1086/683696
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐Dependent, Therapeutic Potential of Angiotensin‐(1–7) for the Treatment of Pulmonary Arterial Hypertension

Abstract: The effects of the heptapeptide angiotensin-(1-7) (Ang-(1-7)), via its receptor Mas, oppose many of the effects of the classic angiotensin II signaling pathway, and pharmacological exploitation of this effect is currently actively pursued for a wide range of cardiovascular, neoplastic, or immunological disorders. On the basis of its vasodilatory and antiproliferative properties, Ang-(1-7) has consequentially also been proposed as a novel therapeutic strategy for the treatment of pulmonary arterial hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Furthermore, stud ies in animal models have shown that administration of angiotensin 1-7 included in cyclodextrin complexes has neuroprotective effects and improves muscle dam age induced by eccentric cardiac overload [38][39][40][41][42][43][44] . A stable, cyclic analogue of angiotensin 1-7 moderately reduced right ventricular systolic pressure in a rat model of monocrotaline induced PAH, but no significant changes were observed in the medial wall thickness of pulmo nary arterioles 45 . To optimize the protective potential of this angiotensin 1-7 analogue for the treatment of PAH, the compound can potentially be combined with a neprilysin inhibitor or an ACE2 activator 46 ; whether this approach is effective in maintaining high levels of angiotensin 1-7 requires further investigation.…”
Section: Box 1 | Timeline Of the Discoveries Related To The Counter-rmentioning
confidence: 85%
“…Furthermore, stud ies in animal models have shown that administration of angiotensin 1-7 included in cyclodextrin complexes has neuroprotective effects and improves muscle dam age induced by eccentric cardiac overload [38][39][40][41][42][43][44] . A stable, cyclic analogue of angiotensin 1-7 moderately reduced right ventricular systolic pressure in a rat model of monocrotaline induced PAH, but no significant changes were observed in the medial wall thickness of pulmo nary arterioles 45 . To optimize the protective potential of this angiotensin 1-7 analogue for the treatment of PAH, the compound can potentially be combined with a neprilysin inhibitor or an ACE2 activator 46 ; whether this approach is effective in maintaining high levels of angiotensin 1-7 requires further investigation.…”
Section: Box 1 | Timeline Of the Discoveries Related To The Counter-rmentioning
confidence: 85%
“…modulation elicited by PAH, increasing parasympathetic and decreasing sympathetic cardiac activation (445). Although the administration of ANG-(1-7) and cyclic ANG-(1-7) immediately after induction of PAH in rats demonstrated no superiority of the MAS agonists compared with conventional treatments, the route of administration as well as the high doses used, which may have effects via AT1 receptors, suggest caution in interpreting the authors' conclusions (51). On the other hand, these results are important in designing future evaluations of the therapeutic potential of ANG-(1-7) for PAH treatment.…”
Section: E Lungmentioning
confidence: 93%
“…Liu et al overexpressed ACE2 globally via the adenoviral gene delivery, and found no differences in blood pressure between control and ACE2-overexpressing rats [200]. Breitling et al found insignificant therapeutic usefulness of ANG (1–7) in an animal model of experimental pulmonary hypertension [205], whereas Zhang et al reported that activation of Mas during myocardial infarction contributed to, rather than attenuated, ischemia-reperfusion injury in rats [206]. In the latter study, inhibition of Mas G-protein signaling surprisingly improved coronary blood flow, reduced myocardial infarct size, and provided long-term cardioprotection [206].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%